Development of a Science Teaching Module Based on SSCS in the Living Things Classification Concept - Bulilingo, Mohamad Rivaldi; Paramata, Dewi Diana; Latjompoh, Masra; Lamangantjo, Chairunnisah J.; Pikoli, Masrid; Nurhayati, Nurhayati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
A teaching module is a learning tool or design based on a curriculum applied to achieve predetermined competency standards. This research aims to use the ADDIE development model to produce a science teaching module based on search, solve, crate and share (SSCS) on valid, practical and effective living things classification concepts. This research was conducted at SMP Negeri 1 Molibagu involving 24 students in Class VII C. The study showed that the results of validating the Science Teaching Module (STM) based on SSCS from experts achieved a score of 90%, which was included in the very valid category and suitable for use in learning. The practicality of the STM based on SSCS as shown by the implementation of learning during two meetings with a percentage of 93% and included in the very good category, student response reached 81.2% with very good criteria, and student activity with a percentage of 85.5% with good criteria. The effectiveness of the STM based on SSCS is shown by the results of the analysis of learning outcomes tests by obtaining N-Gain values 0.78 with high criteria. Thus, it is concluded that the concept of STM based on SSCS in the living things classification concept has valid, practical, and effective criteria. The research of STM based on SSCS is expected to be developed in other material concepts.